Overexpression of Nta-miR6155 confers resistance to Phytophthora nicotianae and regulates growth in tobacco (Nicotiana tabacum L.) - Yang, Kaiyue; Huang, Yuanyuan; Li, Zexuan; Zeng, Qian; Dai, Xiumei; Lv, Jun; Zong, Xuefeng; Deng, Kexuan; Zhang, Jiankui (Frontiers in Plant Science, 2023)
Tobacco black shank induced by Phytophthora nicotianae causes significant yield losses in tobacco plants. MicroRNAs (miRNAs) play a pivotal role in plant biotic stress responses and have great potential in tobacco breeding for disease resistance. However, the roles of miRNAs in tobacco plants in response to P. nicotianae infection has not been well characterized. In this study, we found that Nta-miR6155, an miRNA specific to Solanaceae crops, was significantly induced in P. nicotianae infected tobacco. Some of predicted target genes of Nta-miR6155 were also observed to be involved in disease resistance. To further investigate the function of miR6155 in tobacco during to P. nicotianae infection, Nta-miR6155 overexpression plants (miR6155-OE) were generated in the 2 This is a provisional file, not the final typeset article Honghua Dajinyuan tobacco variety (HD, the main cultivated tobacco variety in China). We found that the Nta-miR6155 overexpression enhanced the resistance in tobacco towards P. nicotianae infections. The level of reactive oxygen species (ROS) was significantly lower and antioxidant enzyme activities were significantly higher in miR6155-OE plants than those in control HD plants during P. nicotianae infection. In addition, we found that the accumulation of salicylic acid and the expression of salicylic acid biosynthesis and signal transduction-related genes is significantly higher in miR6155-OE plants in comparison to the control HD plants. Furthermore, we found that Nta-miR6155 cleaved target genes NtCIPK18 to modulate resistance towards P. nicotianae in tobacco plants. Additionally, phenotypic analysis of miR6155-OE plants showed that Nta-miR6155 could inhibits the growth of tobacco by suppressing nitrogen uptake and photosynthesis. In conclusion, our findings indicated that miR6155 plays a crucial roles in regulation growth and resistance against P. nicotianae infections in tobacco plants.